Visual Art in Nursery Schools - Ivana Rochovská; Dagmar Krupová (Ignatianum University Press, 2017)
This paper focuses on the possibilities of applying an interpretation of visual art in a nursery school. It defines the concept of visual arts and briefly deals with the issue of an interpretation of visual arts. It presents a preview of the educational project for the children, called Umělci v mateřské škole (Artists in Nursery School), which was published in a complete form within a separate publication. It stresses the importance of implementing visual arts in pre-primary education.